MENIMBANG KUALITAS PENDIDIKAN ISLAM DAN KOMPETENSI MANAJERIAL KEPALA SEKOLA - Een Solihah (Al-Misbah (Jurnal Islamic Studies), 2019)
The quality of educational institutions will not be separated from the quality and managerial competence of the leadership of the institution. The more competent and professional managerial, a principal will bring an effect on the quality of the institution he leads. Because of the importance of the principal's quality and managerial competence, it is regulated in several government regulations. As a manager, the principal must have at least four strategies, namely Plan, do, check, act. In addition, the principal must always be oriented towards quality, so the institution he leads still exists.